Prospects of Low Trophic Marine Aquaculture Contributing to Food Security in a Net Zero-Carbon World - Krause, Gesche; Le Vay, Lewis; Buck, Bela H.; Costa-Pierce, Barry Antonio; Dewhurst, Tobias; Heasman, Kevin G.; Nevejan, Nancy; Nielsen, Pernille; Nielsen, Kåre Nolde; Park, Kyungil; Schupp, Maximilian F.; Thomas, Jean-Baptiste; et al. (Frontiers in Sustainable Food Systems, 2022)
To limit compromising the integrity of the planet, a shift is needed towards food production with low environmental impacts and low carbon footprint. How to put such transformative change towards sustainable food production whilst ensuring food security into practice remains a challenge and will require transdisciplinary approaches. Combining expertise from natural- and social sciences as well as industry perspectives, an alternative vision for the future in the marine realm is proposed. This vision includes moving towards aquaculture mainly of low trophic marine (LTM) species. Such shift may enable a blue transformation that can support a sustainable blue economy. It includes a whole new perspective and proactive development of policy-making which considers, among others, the context-specific nature of allocation of marine space and societal acceptance of new developments, over and above the decarbonization of food production, vis á vis reducing regulatory barriers for the industry for LTM whilst acknowledging the complexities of upscaling and outscaling. This needs to be supported by transdisciplinary research co-produced with consumers and wider public, as a blue transformation towards accelerating LTM aquaculture opportunities in a net zero-carbon world can only occur by considering the demands of society.